Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Sn2+ doping-induced activation of inert adsorption sites in Li/Al-LDHs for selective lithium extraction from brines - Rui Zhang; Chenlu Yan; Jun Chen; Ting Wei; Jianguo Yu; Sen Lin (Chemical Engineering Journal, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Dynamics of multiple rogue waves for (3+1)-dimensional variable-coefficient potential Yu-Toda-Sasa-Fukuyama equation - Yi-Lin Tian; Wen-Yuan Li; Nong-Sen Li; Rui-Gang Zhang; Ji-Feng Cui (Wave Motion, 2025)

Comparative Analysis of Stent-Assisted Versus Non-Stent-Assisted Coiling in the Management of Ruptured Intracranial Aneurysms: A Systematic Review and Meta-Analysis - Yu-Hu Ma; Yong-Lin He; Xiao-Yue Zhang; Rui Shang; Hai-Tao Hu; Ting Wang; Sen Lin; Ya-Wen Pan; Chang-Wei Zhang (Translational Stroke Research, 2025)

Synthesis of Fe-ZSM-5 zeolite from high iron-containing palygorskite with peroxidase-like catalytic performance - Fengya Ran; Meng He; Shiyong Sun; Rui Lv; Sen Lin; Ke Wang; Yevgeny Aleksandrovich Golubev; Olga Borisovna Kotova; Elena Leonidovna Kotova (Applied Clay Science, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

Construction of copper-manganese based aminoclays with significant laccase-like activity and its prominent degradation performance towards bisphenol A - Yifan Zeng; Shiyong Sun; Rui Lv; Ke Wang; Yevgeny Aleksandrovich Golubev; Sen Lin; Faqin Dong; Elena Leonidovna Kotova; Olga Borisovna Kotova (Journal of Environmental Chemical Engineering, 2024)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Characteristics and provenances of rare earth elements and Nd isotopes in surface sediments of mangrove wetlands in the Jiulong River Estuary, China - Bo-sen Weng; Rui-an Wan; Rui-lian Yu; Gong-ren Hu; Yu Yan; Cheng-qi Lin; Hua-bin Huang (Environmental Science and Pollution Research, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Chemical constituents from the fruits of Piper longum L. and their vascular relaxation effect on rat mesenteric arteries - Dan Li; Rui Wang; Xiaohan Cheng; Jianfeng Yang; Yihui Yang; Huichong Qu; Sen Li; Shan Lin; Donghua Wei; Yuhua Bai; Xiaodong Zheng (Natural Product Research, 2022)

Geographic and subsequent biotic isolations led to a diversity anomaly of section Heterotropa (genus Asarum : Aristolochiaceae) in insular versus continental regions of the Sino‐Japanese Floristic Region - Daiki Takahashi; Shota Sakaguchi; Yu Feng; Yuji Isagi; Ying‐Xiong Qiu; Pan Li; Rui‐Sen Lu; Chang‐Tse Lu; Shih‐Wen Chung; Yang‐Shan Lin; Yun‐Chao Chen; Atsushi J. Nagano; et al. (Journal of Biogeography, 2021)
Aim The Sino‐Japanese Floristic Region has extremely high species diversity with respect to temperate plants; however, the reasons for this diversity are poorly understood because most studies have only considered geographic isolation caused by climatic oscillations. In some plant groups, high floral trait diversity and uneven species diversity between insular systems and the continental area suggest other factors may have important roles too. The primary purpose of this study is to reveal how abiotic and biotic factors have shaped the species diversity anomaly of Heterotropa between the insular systems and the continental area. Location The Sino‐Japanese Floristic Region. Taxon Section Heterotropa (genus Asarum ; Aristolochiaceae). Methods Using ddRAD‐seq and chloroplast genome data, we built a time‐calibrated phylogenetic tree including 79 species. We estimated the patterns of floral traits (flowering time and floral size) evolution using macroevolutionary modelling, and tested the correlation of speciation rate with the trait evolution rates. Finally, we estimated the isolation factors of all taxa pairs and sister‐taxa pairs based on distribution range and floral traits. Results Phylogenetic analysis indicated that Heterotropa was diverged into two clades (continental clade and insular clade) in the Miocene, and the major subclades corresponded to geographic entities. Most rate shifts accelerating floral trait's evolution occurred during the Pleistocene period. Evolution rate of floral traits showed positive correlation with the speciation rate. Large proportion of taxa in the insular clade are distributed allopatrically. Several sister pairs showed floral trait divergence with geographic overlap. Main Conclusions The diversification of Heterotropa appears to have been triggered by geographic and climatic events, and subsequent repeated floral trait evolution with and without geographic isolation. Furthermore, the high species diversity in the insular systems would have been formed by the repeated range fragmentations and contractions. Our study demonstrates the importance of multidimensional studies to understand the diversification process of temperate plants in the Sino‐Japanese Floristic Region.

Critical transition of soil bacterial diversity and composition triggered by nitrogen enrichment - Weixing Liu; Lin Jiang; Sen Yang; Zhou Wang; Rui Tian; Ziyang Peng; Yongliang Chen; Xingxu Zhang; Jialiang Kuang; Ning Ling; Shaopeng Wang; Lingli Liu (Ecology, 2020)
Soil bacterial communities are pivotal in regulating terrestrial biogeochemical cycles and ecosystem functions. The increase in global nitrogen (N) deposition has impacted various aspects of terrestrial ecosystems, but we still have a rudimentary understanding of whether there is a threshold for N input level beyond which soil bacterial communities will experience critical transitions. Using high‐throughput sequencing of the 16S rRNA gene, we examined soil bacterial responses to a long‐term (13 yr), multi‐level, N addition experiment in a temperate steppe of northern China. We found that plant diversity decreased in a linear fashion with increasing N addition. However, bacterial diversity responded nonlinearly to N addition, such that it was unaffected by N input below 16 g N·m −2 ·yr −1 , but decreased substantially when N input exceeded 32 g N·m −2 ·yr −1 . A meta‐analysis across four N addition experiments in the same study region further confirmed this nonlinear response of bacterial diversity to N inputs. Substantial changes in soil bacterial community structure also occurred between N input levels of 16 to 32 g N·m −2 ·yr −1 . Further analysis revealed that the loss of soil bacterial diversity was primarily attributed to the reduction in soil pH, whereas changes in soil bacterial community were driven by the combination of increased N availability, reduced soil pH, and changes in plant community structure. In addition, we found that N addition shifted bacterial communities toward more putatively copiotrophic taxa. Overall, our study identified a threshold of N input level for bacterial diversity and community composition. The nonlinear response of bacterial diversity to N input observed in our study indicates that although bacterial communities are resistant to low levels of N input, further increase in N input could trigger a critical transition, shifting bacterial communities to a low‐diversity state.

Growth mechanism of a preferentially oriented mordenite membrane - Gang Li; Rui-sen Lin; Eiichi Kikuchi; Masahiko Matsukata (Journal of Zhejiang University-SCIENCE B, 2005)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)